Technical Consultation on the Integration of Statistical and Agricultural Market Information Services - Batjes-Sinclair, Karen (Technical Centre for Agricultural and Rural Cooperation, 2002)
The objectives of this workshop were to share experiences on running market information systems (MIS)...